The effect of scaffolding training on literary text comprehension among adult ESL learners - Nair, Premalatha (2008)
This study examined the ways ESL teacher trainees from one teacher training institute in Malaysia use scaffolding as a form of learning strategy to comprehend literary texts. The study investigated the types and characteristics of scaffolding and the effectiveness of scaffolding strategy training (SST) as used by teacher trainees of three different levels of proficiency. The study utilized a quasi-experimental design and employed a mixed method of collecting and analyzing data that ran concurrently. In the first phase, 96 subjects were selected based on the proficiency test administered and divided accordingly into the experimental and control groups for the quasi-experimental design. Each group consisted of subjects from three levels of proficiency: high proficiency (HP), low proficiency (LP) and mixed proficiency (MP). In this study, the researcher looked into the possibility of using SST to improve comprehension of literary texts among dyads from the experimental group. A pre- and posttests of comprehension questions based on two short stories were carried out. SST was used as a treatment for the experimental group. Subjects from the control group were exposed to the same short stories through the normal lecture conducted by the lecturer from the teacher training institute. In the second phase, subjects’ interactions (in dyads) from the experimental group were recorded twice: before and after SST. Interviews and diary studies were analyzed to identify the types and characteristics of scaffolding utilized in the meaning making process. SST was conducted for a duration of 2 months involving eight sessions on the experimental group. The training sessions mainly focused on the use of five different types of scaffolding; modeling, feedback, cognitive structuring, questioning and asking for participation. The results of the quasi-experimental study revealed that mixed proficiency subjects from the experimental group out performed their peers from other levels of proficiency. One of the reasons identified from the qualitative study is the choice on the types of scaffolding utilized by the peers. High proficiency participants from the mixed proficiency dyads are seen to use analogy as a form of scaffolding to assist their partners understanding. The scaffolding strategy training was observed to have little impact on subjects from the low and high proficiency levels. The qualitative data analysis identified negative scaffolding among the low proficiency subjects which could contribute to their performance. High proficiency subjects on the other hand, preferred to study alone rather than having discussion with their peers. This preference could lead to over confidence among the high proficiency subjects that led to their low performance in the post test. These findings suggest the need for educators to be aware of the strategies teacher trainees employ and the possibility of peer scaffolding to improve their comprehension.